1992
DOI: 10.1007/bf02245175
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol reduces ethanol-induced motor activity stimulation but not conditioned place preference

Abstract: This experiment examined the impact of a dopamine receptor blocker on ethanol's rewarding effect in a place conditioning paradigm. DBA/2J mice received four pairings of a tactile stimulus with ethanol (2 g/kg, IP), haloperidol (0.1 mg/kg, IP)+ethanol, or haloperidol alone. A different stimulus was paired with saline. Ethanol produced increases in locomotor activity that were reduced by haloperidol. However, conditioned preference for the ethanol-paired stimulus was not affected by haloperidol. Haloperidol alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
33
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 13 publications
16
33
4
Order By: Relevance
“…With regard to the invovement of the D2 receptor in ethanol-CPP, the results are not clear. Ethanol (2.0g/kg)-CPP has recently been shown to be reduced in D2 receptor knockout mice (Cunningham et al, 2000) but not after the D2/D3 antagonist haloperidol treatment (Cunningham et al, 1992b;Risinger et al, 1992). Results of the present study are not consistent with previous studies that demonstrated lower ethanol intake (Phillips et al, 1998) or ethanol-CPP (Cunningham et al, 2000) in D2…”
Section: Discussionsupporting
confidence: 38%
“…With regard to the invovement of the D2 receptor in ethanol-CPP, the results are not clear. Ethanol (2.0g/kg)-CPP has recently been shown to be reduced in D2 receptor knockout mice (Cunningham et al, 2000) but not after the D2/D3 antagonist haloperidol treatment (Cunningham et al, 1992b;Risinger et al, 1992). Results of the present study are not consistent with previous studies that demonstrated lower ethanol intake (Phillips et al, 1998) or ethanol-CPP (Cunningham et al, 2000) in D2…”
Section: Discussionsupporting
confidence: 38%
“…The discrepant findings with D 3 receptor knockout studies might be explained by changes during the development of the genetically modified animal to compensate for the absence of the D 3 receptor. In support of this suggestion are findings that haloperidol-treated animals acquire ethanol CPP normally [234] whereas DA D 2 receptor knockout mice fail to acquire the CPP response [65]. These findings demonstrate that the behavioral effects produced by a receptor antagonist are not always compatible with those produced by genetically deleting the receptor at which the antagonist acts.…”
Section: Effect Of Sb-277011-a On Ethanol Self-administration and Relmentioning
confidence: 78%
“…DA receptor antagonists attenuate the locomotor-activating effects of acute ETOH, suggesting an important role of mesoaccumbal DA neurons in mediating the acute effects of ETOH (Liljequist et al, 1981;Risinger et al, 1992;Shen et al, 1995). Behavioral sensitization after repeated ETOH administration has been demonstrated in rodents (Phillips et al, 1994;Hoshaw and Lewis, 2001;Fish et al, 2002).…”
Section: Introductionmentioning
confidence: 99%